PEREMPUAN DAN TERORISME: KETIDAKHADIRAN FENOMENA FEMALE SUICIDE TERRORISM (FST) DI INDONESIA TAHUN 2009-2015 - Sholukhah, Robiatus; Wahyudi, Fendy Eko (Journal of International Relations, 2019)
FST is a phenomenon of the use of women in suicide attacks. In an era where female suicide terrorism (FST) is on the rise, but why this trend was absent in Indonesia. This study aims to analyzes the absence of women in Indonesian suicide terrorism in 2009 â€“ 2015. Using feminist constructivism theory and the concept of women in the Javanese culture. There are three primary findings from this study that explain the absence of female suicide terrorism in Indonesia in 2009 â€“ 2015. First, organizational analysis shows that terrorist groups in Indonesia view that women should be protected. In this view, men would not involve their wives in danger; second security standards of Indonesian terrorism group as secret organization prohibit its members from divulging their plans of action to anyone, including their wives and children, so jihad is only carried out by men; and third, the nature role of women in the Javanese culture as â€œmacak, masak, and manakâ€ that lead women to work in domestic area.